Supply Chain Management and Optimization in Manufacturing - Pirim, Harun; Al-Turki, Umar.; Yilbas, Bekir Sami.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book introduces general supply chain terminology particularly for novice readers, state of the art supply chain management and optimization issues and problems in manufacturing. The book provides insights for making supply chain decisions, planning and scheduling through supply chain network. It introduces optimization problems, i.e. transportation of raw materials, products and location, inventory of plants, warehouses and retailers, faced throughout the supply chain network.
Introduction -- Supply Chain Management -- Scheduling Models in Supply Chain -- Optimization in Supply Chain.
Keywords: Engineering economics; Engineering economy; Production management; Industrial engineering; Production engineering; Engineering Economics, Organization, Logistics, Marketing; Operations Management; Industrial and Production Engineering